The inflammation-depression link: How social networks buffer or exacerbate risk - Nur Hani Zainal (Brain, Behavior, & Immunity - Health, 2025)
Aims: Major depressive disorder (MDD) is a prevalent mental disorder, and low social support and high strain could impact its long-term symptom severity. Increased inflammation, marked by C-reactive protein (CRP) and fibrinogen, has also been correlated with more MDD symptoms. However, the inflammation-MDD symptom association might vary by social support dimensions. The current study thus examined how social support dimensions moderated the inflammation-MDD severity correlation. Methods: Community adults (N = 1,054) with and without MDD provided plasma samples to measure CRP and fibrinogen levels and completed self-reports of perceived support and strain from family, friends, and partners at Wave 1 (W1). MDD severity was assessed at W1 and Wave 2 (W2, nine-year follow-up). Multiple linear regressions and generalized additive modeling (GAM) assessed how W1 social support dimensions and inflammation levels interacted to predict W2 MDD severity, controlling for clinical and sociodemographic covariates. Results: Increased W1 fibrinogen predicted higher W2 MDD severity in participants with lower (vs. higher) W1 social support and higher (vs. lower) social strain (|standardized β| = 0.18–2.31 vs. 0.01–0.03). Further, increased CRP predicted more MDD symptoms in participants with higher (vs. lower) social strain (|β| = 0.24–0.26 vs. 0.15–0.16). These significant interaction findings were identical in linear and GAM models that accommodate non-linear associations. Conclusions: Results suggested that increased proinflammatory activity indexed by CRP and fibrinogen levels could predict nine-year MDD severity under social strains, consistent with the social signal transduction theory. Improving social support and decreasing social strain might buffer inflammation-related depression.